CD-INDUCED MEMBRANE DAMAGES AND CHANGES IN SOLUBLE PROTEIN ANDFREE AMINO ACID CONTENTS IN YOUNG BARLEY PLANTS - Vassilev, Andon; Lidon, Fernando (Emirates Journal of Food and Agriculture, 2011)
Barley (Hordeum vulgare L., cvs. Obzor and Hemus) plants were grown in a Knop nutrient solution with and without 54 µM Cd2+ for 12 days. Some data concerning the ability of Cd to induce membrane damages as well as changes in protein and free amino acids contents of barley plants from the same cultivars are presented in the this work. The Cd treatment enhanced both membrane lipid peroxidation and leakage of K+ from the tissue as well as decreased chlorophyll content. Cd also diminished the content of soluble protein and glutamic acid in leaves and increased that of aspartic acid and several sress-related free amino acids. The negative effects were stronger expressed in the less tolerant barley cv. Hemus.